Novel antenna concepts via coordinate transformation - Tichit, P.-H.; Burokur, S. N.; Wu, X.; Germain, D.; de Lustrac, A. (Advanced Electromagnetics, 2013)
Coordinate transformation is an emerging field which offers a powerful and unprecedented ability to manipulate and control electromagnetic waves. Using this tool, we demonstrate the design of novel antenna concepts by tailoring their radiation properties. The wave manipulation is enabled through the use of engineered dispersive composite metamaterials that realize the space coordinate transformation. Three types of antennas are considered for design: a directive, a beam steerable and a quasi-isotropic one. Numerical simulations together with experimental measurements are performed in order to validate the coordinate transformation concept. Near-field cartography and far-field pattern measurements performed on a fabricated prototype agree qualitatively with Finite Element Method (FEM) simulations. It is shown that a particular radiation pattern can be tailored at ease into a desired one by modifying the electromagnetic properties of the space around radiator. This idea opens the way to novel antenna design techniques for various application domains such as the aeronautical and transport fields.